Pre- and Post-Transplant Anti-BKV IgG Responses and HLA Associations in BK Virus Reactivation Among Renal Transplant Recipients - Deema Ibrahim Fallatah; Steve Christmas (Immuno, 2025)
BK virus (BKV) reactivation is a significant complication in renal transplant recipients, often leading to BK viremia and BK virus-associated nephropathy (BKVAN), which can compromise graft survival. While the routine monitoring of BKV DNA in blood aids in early detection, identifying pre-transplant risk factors remains a challenge. This study investigates the role of pre- and post-transplant anti-BKV IgG levels and human leukocyte antigen (HLA) alleles in predicting BKV reactivation. The hospital-based cross-sectional study was conducted on 38 renal transplant recipients, stratified into viremic, non-viremic, and BKVAN groups. Anti-BKV IgG levels were measured pre-transplant, at viremia onset, and post-viremia using ELISA. BKV DNA was detected via qPCR, and HLA typing was performed using sequence-specific oligonucleotide probe (SSOP) hybridization. Statistical analyses included Kaplan–Meier survival curves and Cox regression models. Pre-transplant anti-BKV IgG seropositivity was higher in viremic (94%) and BKVAN (100%) patients than in non-viremic recipients (66.6%). Post-transplant IgG levels increased significantly in viremic recipients (p < 0.05). HLA-B44 and HLA-DR15 were significantly associated with increased BKV viremia risk (p = 0.02 and p = 0.01, respectively). Pre-transplant anti-BKV IgG levels and specific HLA alleles influence BKV reactivation risk. These findings highlight the potential for integrating serological and genetic screening into pre-transplant assessments to improve risk stratification and post-transplant monitoring strategies.